Merleau-Ponty: acerca da intencionalidade - Paulo Pimenta Marques (2012)
This study aims at showing the notion of intentionality found in the first works of Maurice Merleau-Ponty. We present Merleau-Ponty's reading of tradition through an hermeneutics of his own. We approach the notions of unthought and operative. Then, we approach the founding period of the author's philosophical project in the thirties. In a constant confrontationwith Descartes' Sixth Metaphysical Meditation, Merleau-Ponty constructs zis intellectual project through the examination of the soul or mind and body relations problem. Through Gabriel Marcel's philosophy of existence and incarnation, he wants to open the dimension of philosophy which was forbidden to thought by the Cartesian dualism. To do so the author uses Max Scheler's notion of affective intentionality, which is the first manifestation of the notion of intentionality in Merleau-Ponty's works. The author recovers the intentional nature of perception and desire by deciding to follow the philosophical alternative of phenomenology. This means that the author wants to question the Cartesian and Kantian idealistic tradition and the reflexive philosophy, so that he can attack the contemporary anthropological emptiness, which removes the active-passive complexity of human being, making it incomprehensible inits unity and its bonds with the world and others. After being related to temporality and subjectivity in Phenomenology of perception, the notion of operative intentionality, the only form of intentionality to achieve some stability, will gradually fade until it approaches an ontological psychoanalysis and gives its place to the notion of quiasm in the author'sunfinished last phase